Metastable-state quaternary energetic material as well as preparation method and application thereof

Through the synergistic action of additive manufacturing technology and nanometal powder, metastable Al/Mg/PTFE/AP quaternary energy-containing materials were prepared, solving the problems of high ignition temperature and carbon residue of the Al/PTFE system, achieving lower reaction temperature and higher energy release efficiency.

CN119912303AActive Publication Date: 2025-05-02BEIJING INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411873444.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-05-02
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing Al/PTFE system has problems such as high ignition temperature, a lot of carbon residue after combustion, and lack of flexible forming processes, which is difficult to meet complex use scenarios and production safety requirements.

Method used

Using additive manufacturing technology, combined with nano-aluminum powder, nano-magnesium powder, PTFE powder and AP powder, metastable Al/Mg/PTFE/AP quaternary energy-containing material is prepared by blending resin binder and organic solvent.

Benefits of technology

The reaction temperature threshold is lowered, the energy release level is improved, the carbon residue is reduced, and self-supporting and structural stability is achieved. It is suitable for the preparation of energy-containing materials in complex shapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912303A_ABST
    Figure CN119912303A_ABST
Patent Text Reader

Abstract

The invention provides a metastable quaternary energetic material and a preparation method and application thereof, and the preparation method comprises the following specific steps: S1, dissolving a resin material in an organic solvent, and heating and stirring to obtain a resin elastic adhesive; s2, sequentially mixing nano aluminum powder, nano magnesium powder, PTFE powder and AP powder to obtain quaternary mixed powder; s3, adding an organic solvent into the quaternary mixed powder obtained in the S2, blending and stirring the quaternary mixed powder and the elastic resin adhesive obtained in the S1 under a heating condition, and performing cold shaping to obtain metastable quaternary energetic slurry; and S4, adding the metastable-state quaternary energetic slurry obtained in S3 into a 3D printer charging basket, adjusting equipment parameters of a 3D printer, and processing to obtain the formed metastable-state Al / Mg / PTFE / AP quaternary energetic material. The quaternary energetic material disclosed by the invention is simple to operate and easy to process and form, can meet personalized production requirements, reduces the ignition temperature of an existing composite system material, and reduces reactant residues at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energetic materials, and relates to a metastable Al / Mg / PTFE / AP quaternary energetic material based on additive manufacturing technology, and a preparation method and application thereof. Background Art

[0002] In recent years, nano-metal powder and fluoropolymer system as a new type of energetic material has attracted wide attention due to its high energy density and chemical reaction energy release. Taking the Al / PTFE (aluminum / polytetrafluoroethylene) metastable composite energetic material, which is currently being studied more, as an example, the combustion heat value of the reaction between aluminum and fluoropolymer can reach 9000kJ·kg -1 The combustion temperature can reach 3500K, and the aluminum fluoride (AlF3) generated by the reaction exists in solid form at room temperature, and the sublimation temperature is around 1300°C. The energy released during the reaction of aluminum and fluorine is sufficient to release aluminum fluoride in gaseous form, which also provides theoretical support for its expanded application in the field of energetic materials.

[0003] However, the common Al / PTFE system generally has the problem of high ignition temperature. At the same time, the Al / PTFE metastable composite energetic material focuses more on combustion during the reaction. On the one hand, it lacks the generation of high-temperature, high-heat and high-pressure gas, and it is not easy to generate a detonation wave; on the other hand, it is easy to leave a large amount of carbon residue after combustion, which is not conducive to the mass production and long-term use of standard equipment. In addition, at this stage, there is still a lack of simple, flexible and easy-to-operate molding processes to meet the increasingly complex use scenarios and safety production requirements of energetic materials. Therefore, it is necessary to seek new technical paths to solve the above problems. Summary of the invention

[0004] In view of this, the embodiments of the present invention provide a metastable Al / Mg / PTFE / AP quaternary energetic material based on additive manufacturing technology and a preparation method and application thereof. Nano-aluminum powder is used as a substrate, and additive manufacturing technology is used to anchor nano-aluminum powder, micron-sized PTFE powder and AP (ammonium perchlorate) powder to collaboratively construct a low-ignition-point active energetic material with self-supporting properties and little carbon residue after combustion.

[0005] To achieve the above-mentioned effects, the first aspect of the present invention provides a method for preparing a metastable quaternary energetic material, comprising the following steps: S1: dissolving a resin material in an organic solvent, and obtaining a resin elastic adhesive by heating and stirring; S2: mixing nano-aluminum powder, nano-magnesium powder, PTFE powder and AP powder in sequence to obtain a quaternary mixed powder; S3: adding an organic solvent to the quaternary mixed powder obtained in S2, and further blending and stirring with the resin elastic adhesive obtained in S1 under heating conditions, and obtaining a metastable quaternary energetic slurry after cold shaping; S4: adding the metastable quaternary energetic slurry obtained in S3 to a 3D printer barrel, adjusting the 3D printer equipment parameters, and processing to obtain a formed metastable Al / Mg / PTFE / AP quaternary energetic material.

[0006] Optionally, S1 specifically includes: S11a: placing epoxy resin in a mixed organic solution of ethyl acetate and butyl acetate; S12a: placing the mixed organic solution obtained in S11a into a magnetic heating stirrer, maintaining the temperature at 40° C., and fully stirring to obtain an epoxy resin adhesive.

[0007] Optionally, S1 specifically includes: S11b: dissolving epoxy resin in an organic mixed solution of ethyl acetate and ethanol, and fully stirring to dissolve to obtain a concentrated epoxy resin solution; S12b: dissolving fluororubber in butyl acetate, maintaining the temperature at 40°C, and heating and stirring to obtain a concentrated fluororubber solution; S13b: mixing the epoxy resin concentrated solution in S11b and the fluororubber concentrated solution in S12b in equal proportions, adding an appropriate amount of butyl acetate to readjust the viscosity, and fully mechanically stirring and mixing to obtain an epoxy resin adhesive.

[0008] Optionally, S2 specifically includes: S21: mixing nano aluminum powder and nano magnesium powder after drying and surface oxidation treatment to obtain Al / Mg nano metal mixed powder; S22: ultrasonically treating the Al / Mg nano metal mixed powder obtained in S21 and PTFE powder in an argon environment, and naturally mixing to obtain Al / Mg / PTFE ternary mixed powder; S23: adding AP powder to the Al / Mg / PTFE ternary mixed powder obtained in S22, and mixing by magnetic stirring at room temperature to obtain Al / Mg / PTFE / AP quaternary mixed powder.

[0009] Optionally, S21 specifically includes: S211: treating nano-aluminum powder and nano-magnesium powder with a dry oxygen-rich air flow at room temperature to obtain Al / Mg nano-metal mixed powder with an oxide layer on the surface; wherein the particle size of the nano-aluminum powder and the nano-magnesium powder are both 100nm, the oxygen content in the oxygen-rich air flow is 60-75%, and the remaining components are inert gases, and the treatment time is 6-12 hours; S212: mixing the nano-aluminum powder and nano-magnesium powder with an oxide layer on the surface according to a proportion, and subjecting them to ultrasonic treatment to fully uniformly disperse the two to obtain a nano-metal mixed powder; wherein the ultrasonic treatment time is 1-2 hours.

[0010] Optionally, the flow rate of the argon gas in S22 is 30-50 ml / min, and the ultrasonic treatment time is 1-2 hours; in the magnetic stirring mixing treatment in S23, the magnetic stirrer stirs at a speed of 30-50 r / min.

[0011] Optionally, the organic solvent in S3 is butyl acetate, the heating and stirring temperature is 65-80° C., and the stirring time is 2-3 hours.

[0012] Optionally, the equipment parameters in S4 include feeding speed, forming speed, and the caliber and length of the nozzle used; wherein the feeding speed is 10-20 mm / s; the nozzle is made of stainless steel, and the nozzle caliber is 0.4-0.8 mm.

[0013] The second aspect of the present invention provides a metastable Al / Mg / PTFE / AP quaternary energetic material prepared according to the preparation method.

[0014] The second aspect of the present invention provides an application of the metastable Al / Mg / PTFE / AP quaternary energetic material in the field of energetic materials.

[0015] The beneficial effects of the present invention are:

[0016] (1) The addition of nano-magnesium powder effectively lowers the reaction temperature threshold of the original system, allowing the prepared Al / Mg / PTFE / AP quaternary energetic material to begin the PIR pre-ignition reaction at a lower temperature. On the basis of ensuring the high energy release and high reaction energy release of the original Al / PTFE system, it cooperates and reacts with nano-aluminum powder to improve the energy release level of the energetic material.

[0017] (2) The energetic material also introduces AP, which, on the one hand, gives the metastable quaternary composite system a higher energy output. It can undergo thermal decomposition reaction at a certain temperature, releasing a large amount of heat, making it easier to reach the pre-ignition reaction temperature to a certain extent. On the other hand, AP produces a large amount of gas during decomposition, and the oxygen produced can react with the remaining carbon residue in the Al / PTFE system for a secondary reaction, greatly improving the gas production and energy utilization of the system and reducing the residual reactants.

[0018] (3) The use of additive manufacturing technology can process the raw materials into the shape of energetic material samples as required. With the help of special nozzles, specific equipment and parameter settings, the prepared metastable quaternary energetic slurry can be used to build a self-supporting, structurally stable tubular energetic emission material.

[0019] Therefore, the metastable Al / Mg / PTFE / AP quaternary energetic material based on additive manufacturing technology has potential application prospects in the field of energetic materials.

[0020] In addition, additional advantages, objects, and features of the present invention will be described in part in the following description, and will become apparent to those skilled in the art after studying the following, or may be learned from the practice of the present invention. The objects and other advantages of the present invention may be realized and obtained by the structures and methods specifically pointed out in the written description and claims and the accompanying drawings.

[0021] Those skilled in the art will appreciate that the objectives and advantages that can be achieved with the present invention are not limited to the above specific description, and the above and other objectives that can be achieved by the present invention will be more clearly understood from the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of this application, and do not constitute a limitation of the present invention.

[0023] Figure 1 Schematic diagram of the process of preparing a metastable quaternary energetic material according to an embodiment of the present invention;

[0024] Figure 2 The oxygen bomb calorimeter test results of the metastable Al / Mg / PTFE / AP quaternary energetic material in the embodiment of the present invention;

[0025] Figure 3 This is a DSC test diagram of the metastable Al / Mg / PTFE / AP quaternary energetic material in an embodiment of the present invention;

[0026] Figure 4 This is a thermogravimetric test diagram of the metastable Al / Mg / PTFE / AP quaternary energetic material in an embodiment of the present invention;

[0027] Figure 5 This is a SEM test image of the metastable Al / Mg / PTFE / AP quaternary energetic material in an embodiment of the present invention;

[0028] Figure 6 The internal ballistic performance test results of the metastable Al / Mg / PTFE / AP quaternary energetic material in the embodiment of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and the accompanying drawings. The schematic embodiments of the present invention and their descriptions are used to explain the present invention, but are not intended to limit the present invention. It should also be noted that, in order to avoid blurring the present invention due to unnecessary details, only structures and / or processes closely related to the solutions according to the present invention are shown in the accompanying drawings, while other details that are not closely related to the present invention are omitted.

[0030] It should be emphasized that the term “include / comprises” when used herein refers to the presence of features, elements, or components, but does not exclude the presence or addition of one or more other features, elements, or components.

[0031] Combination Figure 1 It can be seen that the first aspect of the embodiment of the present invention provides a method for preparing a metastable quaternary energetic material, including the following details: S1: dissolving a resin material in an organic solvent, and obtaining a resin elastic adhesive by heating and stirring; S2: sequentially mixing nano-aluminum powder, nano-magnesium powder, PTFE powder and AP powder to obtain a quaternary mixed powder; S3: adding an organic solvent to the quaternary mixed powder obtained in S2, and further blending and stirring with the resin elastic adhesive obtained in S1 under heating conditions, and obtaining a metastable quaternary energetic slurry after cold shaping; S4: adding the metastable quaternary energetic slurry obtained in S3 to the material barrel of a 3D printer, adjusting the equipment parameters of the 3D printer, and processing to obtain a formed metastable Al / Mg / PTFE / AP quaternary energetic material. Figure 2 As shown in FIG. 1 , it is the oxygen bomb calorimeter test result of the metastable Al / Mg / PTFE / AP quaternary energetic material in this embodiment. From the figure, it can be seen that the high and low calorific values ​​of the system reach nearly 16,000 J / g. This data represents that if the sample is completely burned to release heat energy, only 1g will release 16,000 J of heat, so it is an energetic material with high energy density.

[0032] Optionally, S1 specifically includes: S11a: placing epoxy resin in a mixed organic solution of ethyl acetate and butyl acetate; S12a: placing the mixed organic solution obtained in S11a into a magnetic heating stirrer, maintaining the temperature at 40° C., and fully stirring to obtain an epoxy resin adhesive.

[0033] Optionally, S1 specifically includes: S11b: dissolving epoxy resin in an organic mixed solution of ethyl acetate and ethanol, and fully stirring to dissolve to obtain a concentrated epoxy resin solution; S12b: dissolving fluororubber in butyl acetate, maintaining the temperature at 40°C, and heating and stirring to obtain a concentrated fluororubber solution; S13b: mixing the epoxy resin concentrated solution in S11b and the fluororubber concentrated solution in S12b in equal proportions, adding an appropriate amount of butyl acetate to readjust the viscosity, and fully mechanically stirring and mixing to obtain an epoxy resin adhesive.

[0034] Optionally, S2 specifically includes: S21: mixing nano aluminum powder and nano magnesium powder after drying and surface oxidation treatment to obtain Al / Mg nano metal mixed powder. The reason for introducing nano magnesium powder is that it is more reactive than aluminum powder, has a higher combustion rate, and contributes more to light than aluminum powder; although the thermal conductivity of aluminum is higher than that of magnesium, the reaction of aluminum powder requires a higher heat accumulation, so the combustion rate decreases to a certain extent. The active nano magnesium powder improves the energy release efficiency of the entire energetic material system and can generate higher calorific value and energy. S22: Ultrasonic treatment of the Al / Mg nano metal mixed powder obtained in S21 and PTFE powder are performed under argon environment, and naturally mixed to obtain Al / Mg / PTFE ternary mixed powder.

[0035] In fact, the pre-ignition reaction of the existing Al / PTFE system is nearly 400°C, and the main reaction reaches 500-600°C; in order to solve the problem of high ignition temperature of the system, other metal components (Mg) are added to reduce the initial reaction temperature, making the pre-ignition reaction condition threshold lower and the energetic material system more likely to burn. S23: Add AP powder to the Al / Mg / PTFE ternary mixed powder obtained in S22, and mix by magnetic stirring at room temperature to obtain Al / Mg / PTFE / AP quaternary mixed powder. AP (ammonium perchlorate) is a strong oxidant with diverse functions. It produces a large amount of gas when decomposed. Its decomposition chemical equation is as follows:

[0036] 2NH4ClO4=2NO2↑+4H2O+Cl2↑

[0037] 2NO2=2NO↑+O2↑

[0038] It can be seen that the decomposition of AP not only introduces gases such as nitric oxide and chlorine, but also produces oxygen. The main component of the residue of the existing Al / PTFE system is carbon, which can react with the oxygen produced by AP to produce CO, CO2 and other gases, thereby achieving the effect of reducing carbon residue. The decomposition reaction will also release a lot of heat, which also increases the energy density of the system as a whole. Figure 3The DSC (differential scanning calorimetry) results of the metastable Al / Mg / PTFE / AP quaternary energetic material in this embodiment are shown. It can be seen that with the introduction of AP and Mg, the DSC initial reaction temperature of the system, that is, the first exothermic peak that appears, is around 320°C, while the pre-ignition reaction temperature of the traditional Al / PTFE system is usually around 420°C, which greatly reduces the original reaction threshold of the system, and the reaction can occur under lower conditions. Furthermore, Figure 4 What is shown is the TG (thermogravimetric) curve of the metastable Al / Mg / PTFE / AP quaternary energetic material in this embodiment. It can be seen from the figure that in the initial stage, since no reaction occurred, the mass of the sample did not change much. It may be that some water volatilized but it was not very obvious. When the initial reaction temperature was reached, the sample reacted rapidly and the mass decreased at a very high rate until the reaction ended. The residue of the sample remained at 36%. Compared with the traditional Al / PTFE system, the carbon residue of the reaction was reduced, and the energy output was maximized.

[0039] Optionally, S21 specifically includes: S211: treating nano-aluminum powder and nano-magnesium powder with a dry oxygen-rich air flow at room temperature to obtain Al / Mg nano-metal mixed powder with an oxide layer on the surface; wherein the particle size of the nano-aluminum powder and the nano-magnesium powder are both 100nm, the oxygen content in the oxygen-rich air flow is 60-75%, and the remaining components are inert gases, and the treatment time is 6-12 hours; S212: mixing the nano-aluminum powder and nano-magnesium powder with an oxide layer on the surface according to a proportion, and subjecting them to ultrasonic treatment to fully and evenly disperse the two to obtain a nano-metal mixed powder; wherein the ultrasonic treatment time is 1-2 hours.

[0040] Optionally, the flow rate of argon gas in S22 is 30-50 ml / min, and the ultrasonic treatment time is 1-2 hours; in the magnetic stirring mixing treatment in S23, the magnetic stirrer stirs at a speed of 30-50 r / min.

[0041] Optionally, the organic solvent in S3 is butyl acetate, the heating and stirring temperature is 65-80° C., and the stirring time is 2-3 hours.

[0042] Optionally, the equipment parameters in S4 include feed speed, forming speed, and the caliber and length of the nozzle used; wherein the feed speed is 10-20 mm / s; the nozzle is made of stainless steel, and the nozzle caliber is 0.4-0.8 mm. Additive manufacturing technology is also known as 3D printing technology, which can process raw materials into complex structures at one time to meet specific needs. As the use environment of pyrotechnics becomes more and more complex, and energetic materials themselves do have the problem of difficult forming and processing, the use of additive manufacturing technology can process energetic raw materials into more sophisticated structures to meet customized needs.

[0043] The second aspect of the present invention provides a metastable Al / Mg / PTFE / AP quaternary energetic material prepared according to the preparation method. Figure 5 Shown is a SEM test image of the metastable Al / Mg / PTFE / AP quaternary energetic material in this embodiment;

[0044] Figure 6 The figure shows the internal ballistic performance test results of the metastable Al / Mg / PTFE / AP quaternary energetic material in this embodiment. It can be seen intuitively that the explosion pressure of both Al / PTFE and Mg / PTFE is basically stable at around 250MPa, while the explosion pressure after adding AP can reach nearly 400MPa, and the combustion rate is further improved, which further illustrates that the addition of AP improves the gas production of the Al / PTFE system and improves the combustion performance of the system.

[0045] The third aspect of the present invention provides an application of a metastable Al / Mg / PTFE / AP quaternary energetic material in the field of energetic materials.

[0046] The present invention will be further described in detail below through specific implementation examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0047] Example 1

[0048] First, a resin elastomer adhesive was prepared by dissolving 1 part of epoxy resin in an organic mixed solution of butyl acetate and ethanol in a ratio of 7:3, fully dissolving, and stirring for 3 hours to obtain an epoxy resin concentrated solution; dissolving 1 part of fluororubber F2311 in a sufficient amount of butyl acetate, heating and stirring at 40°C to obtain a fluororubber concentrated solution; mixing the epoxy resin concentrated solution and the fluororubber concentrated solution in equal proportions, adding butyl acetate again to adjust the viscosity, and fully mechanically stirring the mixture at a speed of 30 r / min to obtain a resin elastomer adhesive.

[0049] Then, a high-energy metal mixed solution is prepared, 1 part of nano aluminum powder and 2 parts of nano magnesium powder are pretreated in a dry oxygen-rich gas flow with an oxygen content of 75% for 12 hours, and the temperature is controlled at 25°C to obtain nano aluminum powder and magnesium powder with an oxide layer on the surface, and the nano aluminum powder and nano magnesium powder with an oxide layer on the surface are dry-mixed in a ratio of 1:2, and the two are fully uniformly dispersed by ultrasonic treatment for 2 hours to obtain a nano metal mixed powder. The obtained nano metal mixed powder and PTFE powder are ultrasonically treated for 1.5 hours under an argon gas flow with a gas flow rate of 40 ml / min, and Al / Mg / PTFE ternary mixed powder is obtained after natural blending. AP powder is added to the obtained ternary mixed powder, kept at room temperature, and a magnetic stirrer is used to blend at a speed of 45r / min to obtain Al / Mg / PTFE / AP quaternary mixed powder. Sufficient butyl acetate is added to the obtained Al / Mg / PTFE / AP quaternary mixed powder, and heated and stirred until there are no agglomerated particles on the surface to obtain a high-energy mixed solution.

[0050] Afterwards, the prepared resin elastomer adhesive and high-energy metal mixed solution were blended with butyl acetate as a solvent at 65° C., stirred, and cold-formed to obtain a metastable Al / Mg / PTFE / AP quaternary energetic slurry.

[0051] Finally, the prepared metastable Al / Mg / PTFE / AP quaternary energetic slurry obtained after cold forming was added into the 3D printer barrel, and the equipment parameters were adjusted as follows: feeding speed 10 mm / s. After feeding, secondary mixing, and printing through a nozzle with a diameter of 0.8 mm, the formed metastable Al / Mg / PTFE / AP quaternary energetic material was obtained.

[0052] Example 2

[0053] First, a resin elastomer adhesive is prepared. One part of epoxy resin is dissolved in an organic mixed solution of butyl acetate and ethanol in a ratio of 7:3. The mixture is fully dissolved and stirred for 3 hours to obtain an epoxy resin concentrated solution. One part of fluororubber F2311 is dissolved in a sufficient amount of butyl acetate. The mixture is heated and stirred at 45°C to obtain a fluororubber concentrated solution. The epoxy resin concentrated solution and the fluororubber concentrated solution are mixed in equal proportions, butyl acetate is added again to adjust the viscosity, and the mixture is fully mechanically stirred and mixed at a speed of 40 r / min to obtain a resin elastomer adhesive.

[0054] Then, a high-energy mixed solution is prepared, 1 part of nano aluminum powder and 2 parts of nano magnesium powder are pretreated in a dry oxygen-rich gas flow with an oxygen content of 60% for 8 hours, and the temperature is controlled at 25°C to obtain nano aluminum powder and magnesium powder with an oxide layer on the surface, and the nano aluminum powder and nano magnesium powder with an oxide layer on the surface are dry-mixed in a ratio of 1:2, and the two are fully uniformly dispersed by ultrasonic treatment for 1.5 hours to obtain a nano metal mixed powder. The obtained nano metal mixed powder and PTFE powder are ultrasonically treated for 1 hour under an argon gas flow with a gas flow rate of 30 ml / min, and naturally blended to obtain an Al / Mg / PTFE ternary mixed powder, and AP powder is added to the obtained ternary mixed powder, kept at room temperature, and a magnetic stirrer is used to blend at a speed of 50r / min to obtain an Al / Mg / PTFE / AP quaternary mixed powder. Sufficient butyl acetate is added to the obtained Al / Mg / PTFE / AP quaternary mixed powder, and heated and stirred until there are no agglomerated particles on the surface to obtain a high-energy mixed solution.

[0055] Afterwards, the prepared resin elastomer adhesive and high-energy metal mixed solution were blended with butyl acetate as a solvent at 80° C., stirred, and cooled to obtain a metastable Al / Mg / PTFE / AP quaternary energetic slurry.

[0056] The prepared metastable Al / Mg / PTFE / AP quaternary energetic slurry obtained after cold forming was added into the material barrel of the 3D printer, and the equipment parameters were adjusted as follows: the feeding speed was 15 mm / s, and after feeding, secondary mixing, and printing through a nozzle with a diameter of 0.6 mm, the molded metastable Al / Mg / PTFE / AP quaternary energetic material was obtained.

[0057] Example 3

[0058] First, another method is used to prepare the resin elastomer adhesive. The epoxy resin is placed in a mixed organic solvent of ethyl acetate and butyl acetate in a ratio of 3:1 with a weight that is 5 times the weight of the epoxy resin. The resulting remixed organic solution is placed in a magnetic heating stirrer. The temperature is maintained at 40°C and the mixture is fully stirred at a speed of 40 r / min. After complete dissolution, the resin elastomer adhesive is obtained.

[0059] Then, a high-energy mixed solution is prepared, 1 part of nano aluminum powder and 2 parts of nano magnesium powder are pretreated in a dry oxygen-rich gas flow with an oxygen content of 70% for 12 hours, and the temperature is controlled at 25°C to obtain nano aluminum powder and magnesium powder with an oxide layer on the surface, and the nano aluminum powder and nano magnesium powder with an oxide layer on the surface are dry-mixed in a ratio of 1:2, and the two are fully uniformly dispersed by ultrasonic treatment for 1 hour to obtain a nano metal mixed powder. The obtained nano metal mixed powder and PTFE powder are ultrasonically treated for 1 hour under an argon gas flow with a gas flow rate of 45 ml / min, and Al / Mg / PTFE ternary mixed powder is obtained after natural blending, and AP powder is added to the obtained ternary mixed powder, kept at room temperature, and a magnetic stirrer is used to blend at a speed of 35r / min to obtain Al / Mg / PTFE / AP quaternary mixed powder. Sufficient butyl acetate is added to the obtained Al / Mg / PTFE / AP quaternary mixed powder, and heated and stirred until there are no agglomerated particles on the surface to obtain a high-energy mixed solution.

[0060] Afterwards, the prepared resin elastomer adhesive and high-energy metal mixed solution were blended with butyl acetate as a solvent at 70° C., stirred, and cooled to obtain a metastable Al / Mg / PTFE / AP quaternary energetic slurry.

[0061] The prepared metastable Al / Mg / PTFE / AP quaternary energetic slurry obtained after cold forming was added into the material barrel of the 3D printer, and the equipment parameters were adjusted as follows: the feeding speed was 20 mm / s, and after feeding, secondary mixing, and printing through a nozzle with a diameter of 0.4 mm, the molded metastable Al / Mg / PTFE / AP quaternary energetic material was obtained.

[0062] Comparative Example

[0063] Al / PTFE binary energetic material is prepared using traditional sintering process. 4 parts of nano-aluminum powder and 6 parts of PTFE powder are blended at room temperature to obtain composite powder, and the obtained composite powder is pressed to obtain pressed energetic charge. The pressed energetic charge is then sintered and molded at about 300°C. After cooling, a sintered Al / PTFE mixed energetic charge is formed.

[0064] Table 1: Comparative table of performance tests of metastable Al / Mg / PTFE / AP quaternary energetic materials of the present invention

[0065] Group Pre-ignition temperature (℃) Explosion pressure(MPa) Residue weight of reactants (%) Example 1 322 390 36.4% Example 2 325 390 38.3% Example 3 318 390 35.1% Comparative Example 431 270 42.5%

[0066] As can be seen from Table 1, the above Example 3 is a preferred solution. After the introduction of AP and Mg powder into the Al / PTFE system, the pre-ignition reaction temperature is reduced, and the gas production and explosion pressure of the system are increased. This shows that the addition of Mg powder effectively reduces the initial threshold of the reaction, AP decomposes to produce a large amount of gas, and can react with the carbon residue of the original system to release energy in a secondary reaction, further improving the combustion performance of the system.

[0067] In addition, the metastable Al / Mg / PTFE / AP quaternary energetic material prepared by the present invention meets the requirements of stable combustion performance, high gas production, and efficient energy release, and has certain application value and prospects.

[0068] It should be clear that the present invention is not limited to the specific configuration and processing described above and shown in the figures. For the sake of simplicity, a detailed description of the known method is omitted here. In the above embodiments, several specific steps are described and shown as examples. However, the method process of the present invention is not limited to the specific steps described and shown, and those skilled in the art can make various changes, modifications and additions, or change the order between the steps after understanding the spirit of the present invention.

[0069] In the present invention, features described and / or illustrated for one embodiment may be used in the same or similar manner in one or more other embodiments, and / or combined with or replace features of other embodiments.

[0070] The specific description above further illustrates the purpose, technical solutions and beneficial effects of the invention in detail. It should be understood that the above is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a metastable quaternary energetic material, characterized in that: Including the following details: S1: dissolving a resin material in an organic solvent, and heating and stirring to obtain a resin elastic adhesive; S2: mixing nano aluminum powder, nano magnesium powder, PTFE powder and AP powder in sequence to obtain a quaternary mixed powder; S3: adding an organic solvent to the quaternary mixed powder obtained in S2, and further blending and stirring with the resin elastic binder obtained in S1 under heating conditions, and obtaining a metastable quaternary energetic slurry after cold shaping; S4: adding the metastable quaternary energetic slurry obtained in S3 into the barrel of a 3D printer, adjusting the equipment parameters of the 3D printer, and processing to obtain a formed metastable Al / Mg / PTFE / AP quaternary energetic material.

2. The preparation method according to claim 1, characterized in that: S1 specifically includes: S11a: placing epoxy resin in a mixed organic solution of ethyl acetate and butyl acetate; S12a: The mixed organic solution obtained in S11a is placed in a magnetic heating stirrer, the temperature is maintained at 40° C., and stirred thoroughly to obtain an epoxy resin adhesive.

3. The preparation method according to claim 1, characterized in that: S1 specifically includes: S11b: dissolving the epoxy resin in an organic mixed solution of ethyl acetate and ethanol, and stirring thoroughly to dissolve to obtain a concentrated epoxy resin solution; S12b: dissolving fluororubber in butyl acetate, maintaining the temperature at 40° C., heating and stirring to obtain a fluororubber concentrated solution; S13b: The epoxy resin concentrated solution in S11b and the fluororubber concentrated solution in S12b are mixed in equal proportions, and a proper amount of butyl acetate is added to readjust the viscosity. The epoxy resin adhesive is obtained after sufficient mechanical stirring and mixing.

4. The preparation method according to claim 1, characterized in that: S2 specifically includes: S21: mixing the nano aluminum powder and the nano magnesium powder after drying and surface oxidation treatment to obtain Al / Mg nano metal mixed powder; S22: subjecting the Al / Mg nano-metal mixed powder obtained in S21 and the PTFE powder to ultrasonic treatment in an argon environment, and naturally mixing them to obtain an Al / Mg / PTFE ternary mixed powder; S23: adding AP powder to the Al / Mg / PTFE ternary mixed powder obtained in S22, and mixing by magnetic stirring at room temperature to obtain Al / Mg / PTFE / AP quaternary mixed powder.

5. The preparation method according to claim 4, characterized in that: S21 specifically includes: S211: treating nano aluminum powder and nano magnesium powder with a dry oxygen-rich gas flow at room temperature to obtain Al / Mg nano metal mixed powder with an oxide layer on the surface; The particle sizes of the nano aluminum powder and the nano magnesium powder are both 100 nm, the oxygen content in the oxygen-enriched gas flow is 60-75%, and the remaining components are inert gases, and the treatment time is 6-12 hours; S212: mixing nano aluminum powder with an oxide layer on the surface and nano magnesium powder according to a certain proportion, and subjecting the mixture to ultrasonic treatment to make the two powders fully and evenly dispersed to obtain nano metal mixed powder; Wherein, the ultrasonic treatment time is 1-2 hours.

6. The preparation method according to claim 4, characterized in that: The flow rate of the argon gas in S22 is 30-50 ml / min, and the ultrasonic treatment time is 1-2 hours; In the magnetic stirring mixing process described in S23, the magnetic stirrer stirs at a rotation speed of 30-50 r / min.

7. The preparation method according to claim 1, characterized in that: The organic solvent in S3 is butyl acetate, the heating and stirring temperature is 65-80° C., and the stirring time is 2-3 hours.

8. The preparation method according to claim 1, characterized in that: The equipment parameters in S4 include feed rate and nozzle diameter; Among them, the feeding speed is 10-20mm / s; the nozzle is made of stainless steel, and the nozzle diameter is 0.4-0.8mm.

9. A metastable Al / Mg / PTFE / AP quaternary energetic material prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the metastable Al / Mg / PTFE / AP quaternary energetic material according to claim 9 in the field of energetic materials.

Citation Information

Patent Citations

  • Preparation method of multi-element composite energetic microspheres

    CN114634390A

  • Al / GO / AP composite energetic micro-unit material and preparation method thereof

    CN116120136A

  • Inorganic metal oxide / organic polymer nanocomposites and method thereof

    US20040002566A1

  • High energy blast explosives for confined spaces

    US20070113939A1

  • Nano-composite energetic powders prepared by arrested reactive milling

    WO2005049658A2